Investigation into gyneco-pathological disorders and identification of associated bacteria from the genital organs of cows in Dinajpur, Bangladesh - Hasan, Md. Amirul; Al Mamun, Abdullah; Uddin, A. S. M. Ashab; Hassan, Md. Zakir; Hasan, Mahmudul; Rahman, Md. Hafizur (Journal of Advanced Veterinary and Animal Research, 2015)
The present study was aimed to investigate the gynaeco-pathological disorders by post-mortem and histopathological examination, and to identify the associated bacteria. A total of 310 genital tracts of cows were collected from slaughter house of Dinajpur Sadar Upazilla during April 2009 to March 2010. Among the 310 samples, 31.29% (n=97/310) were affected with endrometritis. Similarly, 8.37% (n=26/310) cystic ovary, 6.77% (n=21/310) ovary hyperplasia, 4.84% (n=15/310) pyometra, 4.84% (n=15/310) parovarian cyst, 4.52% (n=14/310) hydrometra, 4.84% (n=15/310) ovary hypoplasia, 3.55%(n=11/310) ovaro-bursal adhesion, 1.29% (n=4/310) vaginal cyst and 0.66% (n=2/310)) hemorrhagic uterine horn were detected by post-mortem examination, the cases were reconfirmed by histopathological studies. Uterine fluid (n=50) samples were collected, and were subjected for conventional bacteriological culture and biochemical analysis. Escherichia coli and Salmonella sp. could be identified from 30% (n=15/50) and 8% (n=4/50) samples, respectively. In conclusion, various pathological disorders in the female reproductive system of cows are prevalent, that may cause reduction of calf production. http://dx.doi.org/10.5455/javar.2015.b76